2008
DOI: 10.1080/14756360701745478
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpromazine oligomer is a potentially active substance that inhibits humanD-amino acid oxidase, product of a susceptibility gene for schizophrenia

Abstract: D-Amino acid oxidase (DAO), a potential risk factor for schizophrenia, has been proposed to be involved in the decreased glutamatergic neurotransmission in schizophrenia. Here we show the inhibitory effect of an antipsychotic drug, chlorpromazine, on human DAO, which is consistent with previous reports using porcine DAO, although human DAO was inhibited to a lesser degree (K i ¼ 0.7 mM) than porcine DAO. Since chlorpromazine is known to induce phototoxic or photoallergic reactions and also to be transformed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…The aliphatic phenothiazine CPZ is a dopamine D2 receptor antagonist that was introduced in the treatment of schizophrenia in the early 1950s; it also acts as a FAD-competitive inhibitor of hDAAO (K d ¼ 5 lM). 9,17 We here demonstrate that the different ligands affect the conformation and stability of the holoenzyme and apoprotein forms of the human flavoenzyme as well as the cellular concentration of hDAAO differently. We also provide evidence that these ligands do not alter the interaction between hDAAO and pLG72 and that affect the time course of cellular D-serine concentration similarly.…”
Section: Introductionmentioning
confidence: 78%
“…The aliphatic phenothiazine CPZ is a dopamine D2 receptor antagonist that was introduced in the treatment of schizophrenia in the early 1950s; it also acts as a FAD-competitive inhibitor of hDAAO (K d ¼ 5 lM). 9,17 We here demonstrate that the different ligands affect the conformation and stability of the holoenzyme and apoprotein forms of the human flavoenzyme as well as the cellular concentration of hDAAO differently. We also provide evidence that these ligands do not alter the interaction between hDAAO and pLG72 and that affect the time course of cellular D-serine concentration similarly.…”
Section: Introductionmentioning
confidence: 78%
“…22 24) It has been reported that the mechanism by which CPZ can in-hibit DAAO activity was through the replacement of the cofactor FAD with CPZ. 23,24) Because most psychotropic drugs generally possess a planar tricyclic structure, other psychotropic drugs may have some DAAO-inhibitory activity. Therefore, we were interested in evaluating the inhibition of DAAO activity by other antipsychotic drugs prescribed to patients with psychiatric diseases.…”
mentioning
confidence: 99%
“…Other drugs were purchased from Sigma Co. Ltd. (St. Louis, MO, USA), Tokyo Chemical Industries Co. Ltd. (Tokyo, Japan), and Wako Pure Chemical Industries Co. Ltd. (Osaka, Japan). Recombinant hDAO was prepared according to previously described methods (3,13,14), and the hDAO-inhibition assay was performed with D-KYN as a substrate, using methods similar to our previous paper (12).…”
Section: Methodsmentioning
confidence: 99%
“…These IC 50 values were comparable to that (2.41 ± 0.23 μM, n = 3) of MPC, a compound with established DAOinhibitory activity. The precise mechanism responsible for hDAO-inhibition is not clear, but chlorpromazine and risperidone have been reported to inhibit hDAO (13,18,19). The common features of the tested drugs were a heterocyclic moiety and a tertiary amino group.…”
Section: Inhibition Of Dao Activitymentioning
confidence: 99%